Kaizen dan Omotenashi sebagai Budaya Kerja dalam Meningkatkan Kinerja SMK Pusat Keunggulan Nusantara Weru - Abidin, Zaenal; Hindriana, Anna Fitri; Arip, Asep Ginanjar (Empowerment, 2023)
The purpose of holding a work culture activity workshop by Nusantra Weru Vocational School, Cirebon Regency is to train, develop and familiarize yourself with the work culture that applies in the global business and industrial world. Participants were given an understanding of two work cultures that originate from Japan and are global in nature, namely Kaizen and Omotenashi. How are the two work cultures implemented in work as teachers, employees and structural officials at SMK Nusantara Weru, Cirebon Regency. The material is delivered by lecture method, question and answer and recitation using power point media. The recitation was carried out by the participants at their respective homes, starting with technical instructions and examples of making Standard Operating Procedures (SOP). Participants create SOPs according to the main tasks of each participant. During the activity, all participants looked enthusiastic and enthusiastic and determined to apply it as a work culture in improving performance so as to improve the quality of output and outcomes for SMK Nusantara Weru graduates, Cirebon Regency